Wogonin Attenuates Ovalbumin Antigen-Induced Neutrophilic Airway Inflammation by Inhibiting Th17 Differentiation - Rie Takagi; Masaaki Kawano; Kazuyuki Nakagome; Kumiko Hashimoto; Takehiro Higashi; Katsuya Ohbuchi; Atsushi Kaneko; Sho Matsushita (Hindawi Limited, 2014)
Allergic airway inflammation is generally considered to be a Th2-type immune response. Recent studies, however, have demonstrated that Th17-type immune responses also play important roles in this process, particularly in the pathogenesis of neutrophilic airway inflammation, a hallmark of severe asthma. We scrutinized several Kampo extracts that reportedly exhibit anti-inflammatory activity by using in vitro differentiation system of human and mouse naïve T cells. We found that hange-shashin-to (HST) and oren-gedoku-to (OGT) possess inhibitory activity for Th17 responses in vitro. Indeed, wogonin and berberine, major components common to HST and OGT, exhibit Th17-inhibitory activities in both murine and human systems in vitro. We therefore evaluated whether wogonin suppresses OVA-induced neutrophilic airway inflammation in OVA TCR-transgenic DO11.10 mice. Consequently, oral administration of wogonin significantly improved OVA-induced neutrophilic airway inflammation. Wogonin suppressed the differentiation of naïve T cells to Th17 cells, while showing no effects on activated Th17 cells.